2008
DOI: 10.1111/j.1530-0277.2008.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and Sex‐Dependent Effects of Footshock Stress on Subsequent Alcohol Drinking and Acoustic Startle Behavior in Mice Selectively Bred for High‐Alcohol Preference

Abstract: Background Exposure to stress during adolescence is known to be a risk factor for alcohol-use and anxiety disorders. This study examined the effects of footshock stress during adolescence on subsequent alcohol drinking in male and female mice selectively bred for high-alcohol preference (HAP1 lines). Acoustic startle responses and prepulse inhibition (PPI) were also assessed in the absence of, and immediately following, subsequent footshock stress exposures to determine whether a prior history of footshock str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 73 publications
7
49
0
Order By: Relevance
“…Studies with cocaine have shown that a range of stress conditions escalate self-administration in rodent models (Boyson et al 2011; Goeders and Guerin 1994; Haney et al 1995; Tidey and Miczek 1996); however, increases in alcohol consumption are generated by more limited stress parameters (Funk et al 2005; Van Erp et al 2001). While other studies have investigated the stress-alcohol link in mice (Chester et al 2008; Croft et al 2005; Sillaber et al 2002), this is the first to delineate conditions of social defeat stress that reliably lead to escalated voluntary ethanol consumption and self-administration in several cohorts of outbred mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with cocaine have shown that a range of stress conditions escalate self-administration in rodent models (Boyson et al 2011; Goeders and Guerin 1994; Haney et al 1995; Tidey and Miczek 1996); however, increases in alcohol consumption are generated by more limited stress parameters (Funk et al 2005; Van Erp et al 2001). While other studies have investigated the stress-alcohol link in mice (Chester et al 2008; Croft et al 2005; Sillaber et al 2002), this is the first to delineate conditions of social defeat stress that reliably lead to escalated voluntary ethanol consumption and self-administration in several cohorts of outbred mice.…”
Section: Discussionmentioning
confidence: 99%
“…Other modalities of stress (e.g., footshock or restraint) also produce increases in arousal in rodents as measured by the acoustic startle test (Chester et al, 2008; Jiang et al, 2011; Rasmussen et al, 2008). Similar to our results, others have reported stress-induced increases in startle amplitude that last up to ten days post stress exposure (Jiang et al, 2011; Rasmussen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperarousal is a hallmark behavioural effect of stress and also of alcohol dependence (Chester et al, 2008; Chester et al, 2005; Davis et al, 2010; Koob, 1999). The acoustic startle response (ASR) is a reflexive reaction to an auditory stimulus that is mediated by the caudal pontine reticular nucleus (Koch, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining physical stressors as animal models of traumatic stress have found mixed results when examining alcohol consumption post-stress. In mice selectively bred for high-alcohol preference (HAP1 lines), footshock stress increases alcohol drinking during adolescence but not adulthood (Chester et al , 2008). Logrip and Zorrilla (2012) have shown that low-drinking animals with a history of stress exposure (light-cued footshock) significantly increased alcohol self-administration following a period of time, suggesting that prior stress exposure sensitizes low drinkers to self-administer alcohol during a subsequent relapse session.…”
Section: Physical Stressorsmentioning
confidence: 99%